Modelling and Simulation Exploring Dynamic System Behaviour - Birta, Louis G.; Arbez, Gilbert (Springer London : Imprint: Springer, 2007)
The application of modelling and simulation is unconstrained by discipline boundaries. It provides support for the planning, design and evaluation of system behaviour, as well as the evaluation of strategies for dynamic system transformation and change. Modelling and Simulation: Exploring Dynamic System Behaviour provides the reader with a balanced and integrated presentation of the modelling and simulation activity for both Discrete Event Dynamic Systems (DEDS) and Continuous Time Dynamic Systems (CTDS). Unconstrained by discipline boundaries, this book presents the fundamentals necessary to understand the many important facets of the modeling and simulation methodology. For example, a novel project-oriented approach clearly reveals the dependency of model structure and granularity on project goals. Features include: • A goal (i.e. project) oriented approach for developing the modelling and simulation methodology • Simulation program development is illustrated in a variety of programming environments • Extensively illustrated with numerous practical examples and useful optimization algorithms • Presentation and use of a novel conceptual modelling approach for DEDS • Describes the process for incorporating parameter optimization into the modeling and simulation activity • Includes primer appendices for each of two (public domain) simulation software environments • Public domain simulation software and a variety of teaching support material are available at a website maintained by the authors Written for students taking a first course in modelling and simulation at either the senior undergraduate & junior graduate levels, this interdisciplinary presentation provides an essential foundation on the topic. It is also ideally suited for self-study by professionals and others who require insight into the features and potential of this rapidly evolving problem solving paradigm.